Sociocultural space in V. Nabokov’s novel "Camera Obscura" - Tatiana G. Mastepak; Elena A. Poleva (Семиотические исследования)
The article substantiates the theoretical and methodological foundations for analyzing the socio-cultural space in works of modernist aesthetic nature. The analysis of the socio-cultural space in the novel Camera Obscura focuses on three aspects: first, the study of the socio-cultural semantics of spatial images; second, the organization of socio-cultural space in the dynamics of plot development; and third, the study of the characters within this space, focusing on the socio-cultural aspect of each character individually and in the system of their relationships. An analysis of the socio-cultural semantics of spatial images makes it possible to reconstruct Nabokov’s ideas about the way of life in European society in the 1920s in general, and more specifically about the central characters – vivid representatives of different social strata (bourgeois intelligentsia, creative bohemians, proletariat). At the same time, the social aspect interests Nabokov in the context of the relationship between the socio-cultural and the individual. The writer shows the impossibility of spiritual growth and creative development in a socially insignificant and internally petty personality (Magda), even within a changing socio-cultural environment, as well as the failure of a personality blind to the surrounding world, who completely replaces social and everyday perception with aesthetic perception (Kretschmar). Horn’s position is also overturned: he possesses a keen vision, both social and creative, but uses it to "cartoonize" life. Nabokov punishes the immoral artist by turning him from a creator of caricatures into a character within a caricature scene, embodied not in creativity, but in social reality.